Pengaruh Cara Pengeringan Oven Dan Microwave Terhadap Perolehan Kadar Senyawa Fenolat Dan Daya Antioksidan Dari Herba Meniran (Phyllanthus niruri L.) - Zet Rizal; Fitri Ledia; Harrizul Rivai (Jurnal Farmasi Higea, 2010)
Effect of drying method in gaining of extractive, phenolic content and antioxidant activity from Phyllanthus niruri (Linn.) leaves have been investigated by UV-Visible spectrofotometric. The drying method tested were air-drying, microwave drying and oven drying at 400C. The determination of phenolics compounds was carried out accourding to Folin Ciocalteau method and antioxidant activity was evaluated by DPPH as oxidant and gallic acid as reference. The determination of extractive compounds showed that the air-drying, microwave drying and oven drying at 40 0C countained 17.54 %; 11.84 %; 14.22 % with the water content 8.2%; 6.6%; 6.7%. The phenolic compounds 2,63900 %; 2,24585 %; 2,28095 %. Then IC50 of the sample were 0.49 mg/mL, 0.51 mg/mL, 0.53 mg/mL respectively.